Pengaruh Aromaterapi Lemon terhadap Nausea And Vomiting pada Ibu Hamil di Puskesmas Mersip Kabupaten Sarolangun Tahun 2024 - Defi Uprianti Bakri; Vevi Endriani; Astari Seto (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
WHO in 2015 also recorded that the number of cases of emesis gravidarum reached 12.5% ​​of all pregnancies in the world, while the incidence of hyperemesis gravidarum was between 0.3-3.2% of all pregnancies in the world. The aim of this research is to determine the effect of lemon aromatherapy on nausea and vomiting in pregnant women at the Public Health Center of Mersip in 2024. The research was conducted using a quasi-experimental approach with one group pre-post test. The location of this research was carried out at the Public Health Center of Mersip and when this research was carried out in January 2024. The population in this study was all 184 pregnant women who were or visited the Public Health Center of Mersip from November 2023 to January 2024. pregnant women, and a sample of 34 people using purposive sampling technique. The data analysis used is univariate and bivariate analysis using the Paired T-Test.The majority of 21 respondents (61.8%) before being given lemon aromatherapy, the majority of 20 respondents (58.8%) experienced moderate nausea and vomiting after being given lemon aromatherapy, and there was a significant difference between nausea and vomiting before and after using lemon aromatherapy as shown by a p value of 0.000. The conclution of these reaseach is an effect of lemon aromatherapy on nausea and vomiting at the Public Health Center of Mersip. It is hoped that lemon aromatherapy can be considered as a permanent SOP for the care of pregnant women with nausea and vomiting and lemon can be recommended as an intervention in midwifery care for pregnant women with nausea and vomiting.